Behavior of innovative circular ice filled steel tubular stub columns under axial compression. (20th May 2018) - Wang, Yanlei; Chen, Guipeng; Wan, Baolin; Lin, Hao; Zhang, Jin
Highlights: Circular ice filled steel tubular (IFT) columns are firstly proposed. Effects of diameter-to-thickness ratios of steel tubes on the compressive behavior of the IFT columns are studied. An increase in diameter-to-thickness ratio leads to a decrease in the bearing capacity and the ductility of the IFT columns. Equations for predicting the load bearing capacity of the IFT columns are proposed. Abstract: The use of conventional building materials has many limitations in cold regions. Inspired by the idea of concrete filled steel tube (CFT), a new form of construction component named ice filled steel tube (IFT), which effectively combines the advantages of both ice and steel tube, was innovatively proposed in this study. This paper presents an experimental study on circular IFT stub columns under axial compression. The main parameter of the test specimens is the diameter-to-thickness ( D / t ) ratio of the steel tube. A total of 12 specimens including 3 plain ice columns and 9 circular IFT columns were divided into four series and tested under axial compression. The test results showed that the development of cracks in ice was delayed by the steel tube. As a result, both the ultimate bearing capacity and the ductility of the ice column were improved due to the confinement from the steel tube. The local bucking at the bottom of the steel tube was also delayed by the ice core. Therefore, the circular IFT column has good potential to serve as a structural component in cold regions.